2020
DOI: 10.1001/jamanetworkopen.2019.19545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Comorbidity Treatment and Costs Associated With Bariatric Surgery Among Adults With Obesity in Canada

Abstract: IMPORTANCE Information on the associations between barriers to delivery of bariatric surgery and poor weight trajectory afterward is lacking. Estimates are needed to inform decisions by administrators and clinicians to improve care. OBJECTIVE To estimate the difference in patient-years of treatment for diabetes, hypertension, and dyslipidemia and public-payer cost between the Canadian standard and an improved bariatric surgery care pathway. DESIGN, SETTING, AND PARTICIPANTS Economic evaluation of a decision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Data from the UK National Bariatric Surgery Registry establish that at the time of primary surgery 53.9% of men and 41.4% of women already have a high level of co-existing disease (defined as 4 or more obesity-related diseases) [20]. Previous studies have also demonstrated that improving pathways to bariatric surgery can reduce the healthcare burden upon individuals and lead to overall healthcare cost savings [21].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the UK National Bariatric Surgery Registry establish that at the time of primary surgery 53.9% of men and 41.4% of women already have a high level of co-existing disease (defined as 4 or more obesity-related diseases) [20]. Previous studies have also demonstrated that improving pathways to bariatric surgery can reduce the healthcare burden upon individuals and lead to overall healthcare cost savings [21].…”
Section: Introductionmentioning
confidence: 99%
“…A previous analysis considered cost and disease treatment outcomes in Canada for SG surgery (13). While SG appears to be increasing in use around the world, including in Canada (5), RYGB continues to be a widely applied surgery in the Canadian setting, although its application varies widely by province.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of a weight loss program in bariatric surgical programs across Canada is unknown. A previous study considered mild weight gain in the presurgical period ( 13 ), but as a more conservative approach in the present analysis, patients are taken to have stable weight on average; the sensitivity analysis includes possibilities of weight gain and weight loss during the presurgical period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have measured the medical costs incurred by patients with bariatric surgery in other countries [28][29][30][31][32] . Nevertheless, different healthcare systems and analytic perspectives made these results not generalizable to the UK.…”
Section: Introductionmentioning
confidence: 99%